Assessing Human Resource Competence In Financial Management Among MSME Actors In Makassar City - Muhaidir Ikram; Fitriani Rahim; Andi Nurfiana Haz (Institute of Advanced Knowledge and Science, 2026)
This study aims to describe human resource competence in financial management among Micro, Small, and Medium Enterprise (MSME) actors in Makassar City. A quantitative descriptive approach was employed using a structured questionnaire distributed to MSME owners and managers who were directly involved in managing business finances. The research instrument measured eight indicators of financial management competence, namely knowledge of business financial management, ability to record financial transactions, ability to prepare financial planning, cash-flow management skills, ability to control business expenditures, discipline in managing business finances, responsibility for financial decision-making, and willingness to improve financial management competence. The data were analyzed using descriptive statistics, including frequency, percentage, mean score, and category interpretation. The validity and reliability tests confirmed that all questionnaire items were valid and reliable. The findings show that MSME actors in Makassar City generally have a high level of perceived competence in financial management. The strongest aspects were willingness to improve financial management competence and responsibility for financial decision-making, indicating positive learning orientation and financial accountability among MSME actors. However, financial planning and cash-flow management require further strengthening. The study implies that MSME development programs should focus not only on general financial literacy, but also on practical training in bookkeeping, cash-flow planning, budgeting, expenditure control, and simple digital financial applications.